Switching on Endogenous Metal Binding Proteins in Parkinson’s Disease - Fleur A. McLeary; Alexandre N. Rcom-H’cheo-Gauthier; Michael Goulding; Rowan A. W. Radford; Yuho Okita; Peter Faller; Roger S. Chung; Dean L. Pountney (Cells, 2019)
The formation of cytotoxic intracellular protein aggregates is a pathological signature of multiple neurodegenerative diseases. The principle aggregating protein in Parkinson’s disease (PD) and atypical Parkinson’s diseases is α-synuclein (α-syn), which occurs in neural cytoplasmic inclusions. Several factors have been found to trigger α-syn aggregation, including raised calcium, iron, and copper. Transcriptional inducers have been explored to upregulate expression of endogenous metal-binding proteins as a potential neuroprotective strategy. The vitamin-D analogue, calcipotriol, induced increased expression of the neuronal vitamin D-dependent calcium-binding protein, calbindin-D28k, and this significantly decreased the occurrence of α-syn aggregates in cells with transiently raised intracellular free Ca, thereby increasing viability. More recently, the induction of endogenous expression of the Zn and Cu binding protein, metallothionein, by the glucocorticoid analogue, dexamethasone, gave a specific reduction in Cu-dependent α-syn aggregates. Fe accumulation has long been associated with PD. Intracellularly, Fe is regulated by interactions between the Fe storage protein ferritin and Fe transporters, such as poly(C)-binding protein 1. Analysis of the transcriptional regulation of Fe binding proteins may reveal potential inducers that could modulate Fe homoeostasis in disease. The current review highlights recent studies that suggest that transcriptional inducers may have potential as novel mechanism-based drugs against metal overload in PD.